Alternating Dynamics of oriC, SMC, and MksBEF in Segregation of Pseudomonas aeruginosa Chromosome - Hang Zhao (American Society for Microbiology, 2020)
ABSTRACT Condensins are essential for global chromosome organization in diverse bacteria. Atypically, the Pseudomonas aeruginosa chromosome encodes condensins from two superfamilies, SMC-ScpAB and MksBEF. Here, we report that the two proteins play specialized roles in chromosome packing and segregation and are synthetically lethal with ParB. Inactivation of SMC or MksB affected, in a protein-dependent manner, global chromosome layout and its timing of segregation and sometimes triggered a chromosomal inversion. The localization pattern was also unique to each protein. SMC clusters colocalized with oriC throughout the cell cycle except shortly after origin duplication, whereas MksB clusters emerged at cell quarters shortly prior to oriC duplication and stayed there even after cell division. The relocation of the proteins was abrupt and coordinated with oriC dynamic. These data reveal that the two condensins play distinct dual roles in chromosome maintenance by organizing it and mediating its segregation. Furthermore, the choreography of condensins and oriC relocations suggest an elegant mechanism for the birth and maturation of chromosomes. IMPORTANCE Mechanisms that define the chromosome as a structural entity remain unknown. Key elements in this process are condensins, which globally organize chromosomes and contribute to their segregation. This study characterized condensin and chromosome dynamics in Pseudomonas aeruginosa, which harbors condensins from two major protein superfamilies, SMC and MksBEF. The study revealed that both proteins play a dual role in chromosome maintenance by spatially organizing the chromosomes and guiding their segregation but can substitute for each other in some activities. The timing of chromosome, SMC, and MksBEF relocation was highly ordered and interdependent, revealing causative relationships in the process. Moreover, MksBEF produced clusters at the site of chromosome replication that survived cell division and remained in place until replication was complete. Overall, these data delineate the functions of condensins from the SMC and MksBEF superfamilies, reveal the existence of a chromosome organizing center, and suggest a mechanism that might explain the biogenesis of chromosomes.